Nilai-nilai Pendidikan Karakter dalam The Ramayana Karya R.K. Narayan - Dewi Nurnani (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2022)
The research entitled “Nilai-Nilai Pendidikan Karakter Dalam The Ramayana Karya R.K. Narayan” is to describe how the values   of character education contained in a book by Indian author, R.K. Narayan, entitled The Ramayana, A Shortened Modern Prose Version of The Indian Epic. The values   of character education, at this time, are very urgent to be given especially to all children of the nation as the future generation because in this era of IT (Information technology) everything can be accessed easily so there needs to be a filter so as not to cause unwanted effects. This study uses a qualitative descriptive method with a structural approach through the study of the intrinsic elements in the book. Data obtained through literature study and direct interviews with resource persons. The results of this study indicate that the plot / storyline of the Ramayana begins with the kidnapping of Sita by Ravana, then a conflict occurs, namely the war between Rama and the monkey army with Ravana and his giant army, with the climax of Ravana’s death in the battlefield. The characters involved are the protagonists, namely Rama, Sita, Lakshmana, Hanuman, and Vibishana, while the antagonists are Ravana, Kumbakarna, Soorpanaka, and Keikayi. The values   of character education contained in the story include the values   of religiosity, nationalism, independence, mutual cooperation, and integrity.